DESAIN ULANG ANTARMUKA MENU PENDAFTARAN DAN PELAPORAN LB 4 PADA SISTEM INFORMASI PUSKESMAS DI PUSKESMAS PAKEM YOGYAKARTA - , SAQIL AHMAD, Nur Rokhman, S.Si., M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Management Information Systems of Health Center (SIMPUS) is a human order that provides information and tools to assist in the management of health centers reaching the target activities. SIMPUS in Pakem not meet the needs of the health center. Some userâs needs which have not been fulfill by SIMPUS among others: 1) the registration officer to register the patient physiotherapy and psychology to public poly because there are no corresponding items with care clinics